MENYOAL KEPASTIAN HAK ATAS TANAH MASYARAKAT MELAYU ASLI: KAWASAN PESISIR KEPULAUAN REMPANG, BATAM BERDASARKAN KONSEPSI HUKUM AGRARIA NASIONAL - Ridha Wahyuni; Taupiqqurrahman Taupiqqurrahman; Ulfia Hasanah (Jurnal Hukum Mimbar Justitia, 2023)
The absence of legal certainty regarding the status of control and ownership of land by the indigenous Malay Rempang community means this condition has the potential to cause land ownership conflicts between the indigenous Malay community and the local government. On the one hand, the government claims that all land in the Batam authority area is state land so that the state has the authority to use it based on Management Rights status, but on the other hand, the community insists that the land they have lived on is the land inherited from their ancestors. If we refer to the concept of land control by the state based on the UUPA then the state in this context is only the party given the authority to regulate and determine land ownership rights and ownership of land rights can only be given to the community, including the rights of indigenous people. Therefore, the native Malay Rempang people who have lived for a long time on their ancestral land must receive protection from the government. The formulation of the problem in this research is; "Whether the native Rempang Malay community in the Rempang coastal area is an indigenous people and what form of protection of land rights for the Rempang native Malay community is based on the concept of national agrarian law." The method used in this research is juridical-informative with a descriptive-analytical approach, using secondary data. The results of the research show that the indigenous Malay community who inhabit the Rempang coastal area can be categorized as a customary law community because their existence fulfills the elements of a customary law community in accordance with applicable legislation so that it is an obligation for the local government to carry out further identification and verification. in order to provide recognition and confirmation of their existence as indigenous people who have legal relations with their customary rights.Keywords: Indigenous People, Land, Rights Protection.